2022
DOI: 10.1007/s00484-022-02288-0
|View full text |Cite
|
Sign up to set email alerts
|

A first approach to human biometeorology research in Brazil: a systematic review and meta-analysis

Abstract: This systematic review aims to give an overview of the diversity of research areas related to human biometeorology in Brazil. The main focus of this paper addresses research trends, represented by published papers with national and international authorship, main contributions and shortcomings, as well as challenges and prospects of research in this area of study. An extensive literature search was conducted in the Scopus, Web of Science, and Science Direct databases so as to identify relevant publication outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 126 publications
0
8
0
Order By: Relevance
“…The symposium was organized by a research collaboration on human biometeorology started in 2021 in the country by a group of Brazilian researchers that culminated in a joint systematic review (Krüger et al, 2022).…”
Section: The First Brazilian Symposium On Human Biometeorologymentioning
confidence: 99%
See 2 more Smart Citations
“…The symposium was organized by a research collaboration on human biometeorology started in 2021 in the country by a group of Brazilian researchers that culminated in a joint systematic review (Krüger et al, 2022).…”
Section: The First Brazilian Symposium On Human Biometeorologymentioning
confidence: 99%
“…More importantly, the first Brazilian Symposium on Human Biometeorology aimed to promote human biometeorology research conducted in the country and to identify knowledge gaps reported in a comprehensive systematic literature review (Krüger et al, 2022).…”
Section: The First Brazilian Symposium On Human Biometeorologymentioning
confidence: 99%
See 1 more Smart Citation
“…The role of climate on health has been known for millennia, yet the deliberate study of the aetiology and statistical analysis have been more recent, and a key component of biometeorology, since the inception of the society and the first issue of the journal (Tromp 1956 ). Increased incidence of respiratory and cardiovascular disease (CDC 2022 ), injuries and early deaths from extreme weather events (CDC 2022 ), changes in the prevalence and geographic distribution of food- and water-borne illnesses and other infectious diseases, and threats to mental health are some of the health effects that are worsened by a change in climate (CDC 2022 ; Krüger et al 2022 ). Changes in climate and climatic variability, particularly changes in the frequency, intensity, and distribution of weather extremes, affect the environment that provides us with clean air, food, water, shelter, and security (Wu et al 2016 ; Wang et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review conducted on studies published in the last decades in Brazil in human biometeorology identified gaps in knowledge [18] that should be filled. The systematic review was based on an extensive literature search in Scopus, Web of Science and Science Direct from the late 1990s until July 2021.…”
Section: Introductionmentioning
confidence: 99%